Rectal neuroendocrine tumor during anorectal surgery: three case reports and a review of the literature - Dong, Ruoxi; Lu, Jingen; Zhou, Hao; Dong, Qingjun; Wang, Chen (Frontiers in Oncology, 2025)
BackgroundRectal neuroendocrine tumors (NET) are thought to originate from the diffuse neuroendocrine system. The lack of apparent signs of illness and the patient’s non-specific presentations often cause a delay in diagnosis, until in their final stages of cancer. Thus, rectal NETs pose a significant challenge to most physicians.Case presentationThis article presents three cases of rectal NETs discovered during anorectal surgery. Owing to their atypical symptoms, they were initially diagnosed as mixed hemorrhoids or perianal fistulas. However, the patients were diagnosed with rectal NETs and thus underwent endoscopic dissection or transanal endoscopic microsurgery. Histological analysis revealed three rectal NETs, one G1 and two G2. All patients were followed-up for more than 6 months, with excellent outcomes without recurrence.ConclusionsThe etiology, pathogenesis, therapeutic methods, prevention, and prognosis of rectal NETs remain challenging. Given the variable understanding of the most appropriate operative approaches for rectal NETs, our objective was to broaden the perspective of this infrequent disease by delivering distinctive individual experiences and emphasizing the therapeutic significance of delicate surgery.